Systematic Literature Review: Strategic Application of Talent Management In Organisations - Rachmawan, Ahmad; Tussoleha Rony, Zahara; Ali, Hapzi (Dinasti International Journal of Management Science, 2024)
Talent is considered as the potential or ability that varies from person to person when planning organizational development programs and is a concept that is still debated in modern times. If managed well, talented human resources will support the implementation of the organization's growth strategy and contribute to achieving organizational goals and economic growth. The research method uses SLR based on the reporting items selected for the systematic review. The findings show that talent management and retention is considered a top business priority, and organizations want to evaluate the performance of these employees to increase organizational commitment and avoid market defection.